Managing financial globalization: A guide for developing countries based on the recent literature - Shang-jin Wei (Asian Development Bank Institute (ADBI), 2018)
This paper seeks to draw lessons for developing countries based on a survey of the recent literature on financial globalization. First, while capital account openness holds promises (by potentially generating a lower cost of capital, better risk sharing, and stronger disciplines on policies), they do not always work out that way in the data. Distortions in the domestic financial market, international capital market, domestic labor market, and domestic public governance can all make financial globalization less beneficial for developing countries. Second, developing countries sometimes need to insulate themselves from foreign monetary policy shocks. The empirical pattern appears to be somewhere between a trilemma and a dilemma. While nominal exchange rate flexibility is insufficient for policy autonomy, capital flow management may be needed to confer more monetary policy autonomy.
Keywords: E42; E43; E52; 330; financial globalization; monetary policy autonomy; overborrowing; capital flow management